2003
DOI: 10.1007/s00467-003-1133-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of mycophenolate mofetil for autoimmune disease in children

Abstract: This study describes the pharmacokinetics of mycophenolate mofetil (MMF) in 15 pediatric patients with vasculitis and connective tissue disease involving the kidney. Patients included 10 with systemic lupus erythematosus (SLE), 1 with antiphospholipid antibody syndrome, 2 with Wegener granulomatosis, and 1 each with Goodpasture syndrome, Henoch-Schönlein-associated nephritis, and 1 with severe tubulointerstitial nephritis and uveitis. All patients were treated with steroids and additional therapy prior to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 18 publications
(11 reference statements)
3
35
2
Order By: Relevance
“…[916] We also observed a similar correlation in our study. However, from our data 61.5% of our patients would have an incorrect dose change if only MPA trough (therapeutic goal: 1–5 μg/ml) was used as a replacement for MPA AUC (0-12) (therapeutic goal we used was 30–60 mg.h/L).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[916] We also observed a similar correlation in our study. However, from our data 61.5% of our patients would have an incorrect dose change if only MPA trough (therapeutic goal: 1–5 μg/ml) was used as a replacement for MPA AUC (0-12) (therapeutic goal we used was 30–60 mg.h/L).…”
Section: Discussionsupporting
confidence: 90%
“…suggested that the trough concentration is a clinically important time point in MPA monitoring and defined a target trough C troughss concentration between 1 and 5 μg/ml in children with autoimmune disease. [16] In comparison, the range of trough concentrations (0.7–5.35 μg/ml) measured in our study was not significantly different. However, it needs to be mentioned that the median ± SD dose used in their study was 25.2 ± 10.6 mg/kg in comparison to the median ± SD of 38.89 ± 9.48 mg/kg used in our patients.…”
Section: Discussioncontrasting
confidence: 71%
“…In the clinic, the steady-state C max for MPA in serum of patients with lupus nephritis has been reported to be 21 μg/ml (66 μM) (29), the C max of MMF in children with autoimmunity, including SLE, is reported to be in the same range, 18.5 μg/ml (28), and the C max of MMF for patients with SLE was found to be 16.6 μg/ml (30). A similar range for transplant patients was reported (27).…”
Section: Discussionmentioning
confidence: 99%
“…There were few side effects including diarrhea and leukocytopenia in one case and viral infections in two cases. They conclude that MMF at 900 mg/m 2 per day appears to be effective in these patients [19]. …”
Section: Discussionmentioning
confidence: 99%